(untitled) (Aristonothos. Rivista di Studi sul Mediterraneo Antico, 2009)
This brief note focuses on an unpublished seal of the Lyre Player Group found in Tarquinia. This particular class of seals, widespread in the basin of the Mediterranean and reaching the Italian Peninsula during the Orientalizing period, represents a good indicator for the study of the circulation of craftsmen and traders. In particular, this paper presents some considerations about the development of glyptic in Etruria during the Orientalizing period.